A Fluorogenic Screening for Enantio- and Diastereoselectivity of 2-Deoxy-d-ribose-5-phosphate Aldolases - Bisterfeld, Carolin; Küberl, Irene, née Kullartz; Dick, Markus; Pietruszka, Jörg (Synlett, 2016)
A highly sensitive, fluorescence-based selectivity screening system for 2-deoxy-d-ribose-5-phosphate aldolases was realized by installing short, straightforward syntheses to fluorophore-coupled carbohydrates as d-ribose, l-ribose, and d-xylose. The substrates allow the simultaneous determination of enantioselectivity and diastereoselectivity of DERA-catalyzed aldol reactions.
Keywords: 2-deoxy-d-ribose-5-phosphate aldolase; fluorogenic screening; enantioselectivity; diastereoselectivity; extremophilic aldolases